The influence of supplementation with artichoke (Cynara scolymus L.) extract on selected redox parameters in rowers - Skarpanska-Stejnborn, A.; Pilaczynska-Szczesniak, L.; Basta, P.; Deskur-Smielecka, E.; Horoszkiewicz-Hassan, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
High-intensity physical exercise decreases intracellular antioxidant potential. An enhanced antioxidant defense system is desirable in people subjected to exhaustive exercise. The aim of this study was to investigate the influence of supplementation with artichoke-leaf extract on parameters describing balance between oxidants and antioxidants in competitive rowers. This double-blinded study was carried out in 22 members of the Polish rowing team who were randomly assigned to a supplemented group (n = 12), receiving 1 gelatin capsule containing 400 mg of artichoke-leaf extract 3 times a day for 5 wk, or a placebo group (n = 10). At the beginning and end of the study participants performed a 2,000-m maximal test on a rowing ergometer. Before each exercise test, 1 min after the test completion, and after a 24-hr restitution period blood samples were taken from antecubital vein. The following redox parameters were assessed in red blood cells: superoxide dismutase activity, glutathione peroxidase activity, glutathione reductase activity, reduced glutathione levels, and thiobarbituric-acid-reactive-substances concentrations. Creatine kinase activity and total antioxidant capacity (TAC) were measured in plasma samples, lactate levels were determined in capillary blood samples, and serum lipid profiles were assessed. During restitution, plasma TAC was significantly higher (p < .05) in the supplemented group than in the placebo group. Serum total cholesterol levels at the end of the study were significantly (p < .05) lower in the supplemented group than in the placebo group. In conclusion, consuming artichoke-leaf extract, a natural vegetable preparation of high antioxidant potential, resulted in higher plasma TAC than placebo but did not limit oxidative damage to erythrocytes in competitive rowers subjected to strenuous training.